Key Mental Health Challenges: The Role of Health Policy After COVID-19 - Paweł, Juraszek; Karolina, Król; Mateusz, Grajek (Journal of Psychology and Psychotherapy Research, 2024)
Background; The COVID-19 pandemic profoundly impacted global mental health, revealing vulnerabilities in healthcare systems and exacerbating issues such as anxiety, depression, and PTSD. Vulnerable groups, including healthcare workers, young adults, and children, faced heightened risks due to social isolation, economic uncertainty, and disruptions to daily life. These challenges emphasized the critical need for targeted interventions and systemic improvements in mental health care. Objective; This review aims to analyze the key mental health challenges emerging post-pandemic, evaluate the roles of government policies and community interventions, and propose evidence-based strategies for prevention and rehabilitation. Additionally, it highlights innovative solutions to address service gaps and promote resilience. Methodology; A narrative review methodology was employed, synthesizing data from peer-reviewed journals, organizational reports (e.g., WHO, OECD, UNICEF), and national datasets from 2019–2023. Key themes—mental health challenges, government roles, prevention strategies, and innovative interventions—were explored through qualitative and quantitative analyses. Selection criteria focused on mental health conditions exacerbated by the pandemic and policy responses at local and national levels. Conclusions; The pandemic underscored the importance of mental health as a public health priority. Effective interventions include integrating mental health into broader health policies, increasing funding, and promoting public awareness. Prevention strategies focusing on early detection, lifestyle interventions, and community support proved vital, while rehabilitation efforts such as family involvement, peer networks, and technological tools facilitated recovery. A multisectoral, evidence-based approach is essential to build resilient mental health systems capable of addressing future challenges.